WebAssembly potentials: A performance analysis on desktop environment and opportunities for discussions to its application on CPS environment - Souza Junior, João Lourenço; de Oliveira, Davi; Praxedes, Victor; Simiao, Dennys (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais Estendidos do X Simpósio Brasileiro de Engenharia de Sistemas ComputacionaisDO - 10.5753/sbesc_estendido.2020.13104, 2020)
The Web started as a simple document-sharing network and today has evolved to become a consolidated and ubiquitous platform for creation and application distribution. To explore its demands, web browser vendors have been working on new technologies like WebAssembly, a new type of machine language for a conceptual machine instead of a real physical machine, supported by the modern web browsers, providing new features and greater performance for web applications. At the other end, embedded devices have also evolved along with applications. However, there are still semantic heterogeneity, maintainability, and development issues inherent to the vast number of devices and services that operates in the numerous domains of Cyber-Physical Systems (CPS). The overall objective of this work is to study the WebAssembly technology through a performance analysis in a desktop environment, presenting empirical comparisons between the execution of a program compiled in native machine code and the same program compiled in WebAssembly, to verify its flexibility to compile code written in different languages for web applications and maintain similar performance to their native applications counterpart. We also point out the opportunities and challenges to potentially apply WebAssembly as a semantic abstraction layer for embedded devices in CPS development.